Children of the storm - Peters, Elizabeth, 1927-2013 (Peters, Elizabeth, 1927-2013. Amelia Peabody series., 2011)
At last the Great War is over. Amelia, her distinguished Egyptologist husband Emerson and their extended family are preparing for another season of excavation in Egypt. To everyone's great joy their son Ramses and his wife Nefret have become parents. Amelia, enjoying her role of fond (yet firm) grandmother, hopes that for once, this will be a quiet year with Ramses no longer undertaking perilous missions for British intelligence and no old enemies on their trail. Amelia is sadly mistaken. Past dangers cast shadows across the seemingly peaceful present, and a new adversary--unlike any Amelia has ever encountered--will chart a course that puts her beloved family directly in the path of destruction.